Development of an integrated smart monitoring system for enhanced peritoneal dialysis care - Saminu, Sani; Iliyas, Abdulrasaq; Yahaya, Suleiman Abimbola; Muniru, Idris Oladele; Ajibola, Taiye Mary; Ibitoye, Morufu Olusola; Usman, Habib Muhammad; Abdulrazaq, Sanusi (Kathmandu University Journal of Science Engineering and Technology, 2024)
Kidney removes wastes and extra water from the blood as urine and helps to maintain chemical balance in the body. The kidney controls blood pressure and production of red blood cells. When the kidneys are constrained, waste products and fluid build-up in the body system which causes swelling and bloating. Globally, Kidney disease is a great health challenge affecting millions of peoples at all ages. Dialysis is the removal of waste products and excess fluid from the blood when the kidney failed to function properly. Peritoneal dialysis is a home-based renal therapy for removal of excess fluid from the body for patients with constrained kidney. Integrating recent advancement in telemedicine and Internet of Medical Things (IoMT) into the conventional monitoring systems is a very vital in digital health technologies that improve the remote patient monitoring, empower patients, better care outcomes, and minimize cost related issues. The main aim of this paper is to design and integrate a smart monitoring system for supporting peritoneal dialysis care with the help of a sensor monitoring system and the Internet of Things (IoT) technology. Encompassing sensor integration (weight sensor), web application development/cloud-based platform Internet of Things and an API for notifications of real time data using Nodemailer. Emphasis will be placed on developing user-friendly interfaces for both patients and healthcare providers, ensuring easy access to real-time data, treatment reminders and communication channels. The system’s ability to detect such small variations in weight measurements over time demonstrates and supports its suitability for applications requiring precise weight monitoring and management of the dialysate fluid movement in and out of the patient’s systems.